Association of exhaled carbon monoxide with risk of cardio-cerebral-vascular disease in the China Kadoorie Biobank cohort study - Qiu, G; Yu, K; Yu, C; Li, W; Lv, J; Guo, Y; Bian, Z; Yang, L; Chen, Y; Chen, Z; Hu, FB; Li, L; et al. (Springer Nature, 2020)
Exhaled carbon monoxide (COex) level has been proposed as a noninvasive and easily-obtainable cardiovascular risk marker, however, with limited prospective evidence, and its association with stroke risk has been rarely explored. Measurements of COex were performed during 2004-2008 baseline examinations in the China Kadoorie Biobank study among 512,891 adults aged 30-79 years from 10 diverse study areas. After excluding participants with baseline cardiopulmonary diseases, stroke and cancer, 178,485 men and 267,202 women remained. Cox regression yielded hazard ratios (HRs) and 95% confidence intervals (CIs) for risk of cardio-cerebral-vascular disease (CCVD) associated with COex levels, with sequential addition of adjustment for proxy variables for CO exposure, including study area indexing ambient CO variations at large, and smoking and solid fuel use, apart from adjusting for traditional cardiovascular risk factors. During 7-year follow-up, we documented 1744 and 1430 major coronary events (myocardial infarction plus fatal ischemic heart disease), 8849 and 10,922 ischemic strokes, and 2492 and 2363 hemorrhagic strokes among men and women, respectively. The HRs with 95% CIs comparing the highest with lowest COex quintile were 2.15 [1.72, 2.69] for major coronary events, 1.65 [1.50, 1.80] for ischemic stroke, and 1.35 [1.13, 1.61] for hemorrhagic stroke among men, while among women higher associated risk was only observed for major coronary events (1.64 [1.35, 2.00]) and ischemic stroke (1.87 [1.73, 2.01]). The elevated risks were consistent when COex level was over 3 ppm. However, these associations were all attenuated until null by sequential addition of stratification by study areas, and adjustments of smoking and solid fuel use. Nevertheless, the association with ischemic stroke was maintained among the subgroup of male smokers even with adjustment for the depth and amount of cigarette smoking (HR [95% CI]: 1.37 [1.06, 1.77]), while a negative association with hemorrhagic stroke also appeared within this subgroup. Higher COex level (over 3 ppm) was associated with elevated risk of ischemic CCVD, but not independently of CO exposure. Our finding suggests that, though not an independent risk factor, COex could potentially provide a cost-effective biomarker for ischemic cardio-cerebral-vascular risk, given that CO exposure is ubiquitous.